Multi-phantom SAR-assessed ultra-compact dual-band millimeter-wave (mmWave) antenna optimised for 5G smartphones - A. J. A. Al-Gburi (PLoS ONE, 2026)
This paper presents an ultra-compact millimetre-wave antenna designed to support 28 GHz and 38 GHz 5G smartphone applications. To ensure safe and reliable integration, a comprehensive specific absorption rate (SAR) evaluation was carried out using three anatomically realistic head phantoms: a full-head, a skeletal skull, and an isolated brain model. The fabricated prototype demonstrated robust dual-band performance with close agreement between simulated and measured results. Importantly, SAR levels remained well below international safety limits, confirming both compliance and user safety. These results highlight the antenna’s strong potential for enabling next-generation high-data-rate communications in compact mobile devices.